The explorers of Australia and their life-work - Favenc, Ernest, 1846-1908. (Christchurch : Whitcombe & Tombs, 1908)
Annotation pending.
Bibliography: p. [viii]
Keywords: Explorers -- Australia; Australia -- Discovery and exploration; Northern Territory -- Discovery and exploration; Wave Hill Station (N.T.); Australia